STANDARD ANALYSIS OF CITRUS CROPS IN THE SYRIAN ARAB REPUBLIC - M. Khatlish; B. Morsi; M Abdel Fatah (Arab Universities Journal of Agricultural Sciences, 2017)
The study aimed to throw light on the current status of the area, productivity and production of citrus, orange and lemon in Syria, the development of the quantity and value of exports and imports, the export and import price of citrus, the development of the quantity and value of exports and exports price of the orange during the study period, the geographical distribution of Syrian exports of orange for the period (2007-2011), and standard samples for external demand on oranges. The foreign trade of citrus was in Syria the study showed that the production of citrus growing at a rate of about 38.12 thousand tons per year and the cultivated area of citrus growing at of about 1.35 thousand acres per year, the increase in the productivity of the hectare was not significant in any mathematical relation. The production of oranges increased by about 45% per year and the cultivated area of oranges increased by about 0.94 thousand acres per year, the increase in the productivity of the hectare was not substantiated in any mathematical relation. The production of lemons increased by about 6.73 thousand tons per year, growing at of about 0.28 thousand acres per year, the increase in the productivity of the hectare was not substantiated in any mathematical relation during the study period. The quantity of citrus exports increased by 24.9% per year, the value of citrus exports increased by 25.5% per year, the quantity of imports of citrus is increasing at a rate of about 19.5% annually, the value of imports of citrus is increasing at a rate of 24.9%, the quantity of exports of oranges is increasing at a rate of about 23.1% annually and the value of exports of oranges is increasing by 18.1%. The export price of oranges decreased by about $ 22.09 per year. In addition, the factors determining the average per Iraqi capita share of Syrian orange has been studied which indicated inverse relation between the dependent variable and the Syrian export price per kilogram in dollars, with an increase of 1% the average per Iraqi capita share of Syrian orange decreased by 2.45%. As well as a positive relation between the dependent variable and the average per Iraqi capita income in dollar and the export price of Turkey in dollars, by the increase of these factors of 1% the average per capita Iraqi quantity of Syrian orange increased by 1.98% and 1.37%, respectively. In addition, the factors determining the average per Jordanian capita share of Syrian oranges were calculated according to the export price of Syria in dollars. The model shows a positive relationship between the dependent variable and the export price of Lebanon in dollars. The average per Jordanian capita share of Syrian oranges was 2.88% and 0.75% respectively, which shown an inverse relation between the dependent variable and the export price of Syria in dollar, with an increase of 1%, the average per Jordanian capita share of Syrian orange decreased by 4.4%. The most important indicators of foreign trade of Syrian orange for the most important countries showed Russia in the first position in terms of the market share, which is about 96.1% of the total Syrian exports. It is clear that for political reasons between Syria and Russia. Then, Saudi Arabia and Kuwait came second with 1.7% of Syrian exports.